Bridging the Skill Gap: Abhyangakarta (Ayurveda Massage Therapists) Training in Nepal’s Health and Wellness Sector - Bhusal, Nirmal; Ghimire, Bikas Raj; Acharya, Sunita; Prasad, Shiv Mangal (Journal of Training and Development, 2026)
Nepal’s Ayurveda and wellness sector faces a lack of a formally trained workforce of Abhyangakarta (Ayurveda oil massage therapists). Abhyangakarta are employed across central, provincial Ayurveda hospitals, district Ayurveda centers, naturopathy centers, private wellness spas, and tourism resorts. Employing a qualitative approach, including stakeholder interviews and observational audits, the study addresses the human resource gap resulting from the lack of formally trained Abhyangakarta. The existing Abhyangakarta training is not sufficient for national Ayurveda healthcare delivery and wellness tourism. The study also identifies key lacunae as absence of a standardized curriculum, the lack of integration with the labour market, and no clear career pathway. Basic health service is the responsibility of local government and the Abhyangakarta have a scope of getting appointed as therapists in health centers as it is a component of basic health service package. The analysis identifies a need for a nationally accredited, competency based vocational training program integrating core Ayurveda principles, biomedical safety, standardized technical skills, and client management to uplift Ayurveda and wellness services. Initiating the process to formalize Abhyangakarta training is the necessary step to bridge the skill gap and unlock the full potential of Nepal’s Ayurveda health sector and wellness tourism economy.